Pengaruh Lokasi, Kualitas Pelayanan, Fasilitas dan Harga Terhadap Keputusan Berkunjung (Studi pada Wisatawan Ledok Amprong di Kabupaten Malang) - Ryanda Titanio Yunarsyah; Agus Widarko; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract In this day and age, traveling has become part of a lifestyle to reduce boredom and refresh the mind from daily routines. Affordable location, good service quality, adequate facilities and affordable prices are important factors in influencing the decision to visit. The purpose of this study is to determine the influence of location, service quality, facilities and prices on visiting decisions. This research was conducted on Ledok Amprong tourists in Malang Regency. This study used a quantitative approach with sampling techniques using non-probability sampling methods with purposive sampling techniques. Determination of the number of samples as many as 96 respondents. The data analysis methods used are instrument tests, normality tests, classical assumption tests, multiple linear regression analysis, hypothesis tests and coefficients of determination using SPSS 25 software. The results of this study show that location, service quality, facilities and price have a significant effect simultaneously on visiting decisions. Location, service quality and price have a positive and significant effect on the decision to visit, while facilities have a positive and insignificant effect on the decision to visit. The influence of location, service quality, facilities and price on visiting decisions shows a coefficient of determination of 41%. Keywords: Visiting Decision, Location, Quality of Service, Facilities and Price.